2017
DOI: 10.1111/jse.12267
|View full text |Cite
|
Sign up to set email alerts
|

Plant speciation across environmental gradients and the occurrence and nature of hybrid zones

Abstract: Environmental gradients are very common and many plant species respond to them through adaptive genetic change. This can be a first step along a continuum of change that leads ultimately to the origin of fully reproductively isolated forms, i.e., 'biological species'. Before complete reproductive isolation is achieved, hybrid zones may form between divergent lineages either through primary intergradation or secondary contact. Here, I review the literature on plant hybrid zones between native species and highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
147
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(152 citation statements)
references
References 114 publications
(126 reference statements)
5
147
0
Order By: Relevance
“…) and probable hybrid speciation (see Moore & Wen, ). Future work should specially focus on testing hybrid speciation hypotheses using dense sampling of populations (Abbott, ). Additionally, detailed analyses of Vitis based on nuclear phylogenetic results integrated with niche modeling (also see Zimmer & Wen, , ; Wen et al, ; Callen et al, ) and the existing plastome data may shed insight into the biogeographic and demographic dynamics of Vitis from the Tertiary to the present.…”
Section: Future Workmentioning
confidence: 99%
“…) and probable hybrid speciation (see Moore & Wen, ). Future work should specially focus on testing hybrid speciation hypotheses using dense sampling of populations (Abbott, ). Additionally, detailed analyses of Vitis based on nuclear phylogenetic results integrated with niche modeling (also see Zimmer & Wen, , ; Wen et al, ; Callen et al, ) and the existing plastome data may shed insight into the biogeographic and demographic dynamics of Vitis from the Tertiary to the present.…”
Section: Future Workmentioning
confidence: 99%
“…Natural hybrid zones provide evolutionary laboratories to identify chromosomal regions that introgress significantly more frequently than expected (Abbott, ; Buerkle & Lexer, ; Lexer, Heinze, Alia, & Rieseberg, ). Forest tree species with extensive natural hybrid zones, large ranges across geographical and climatic clines as well as substantial trait variation (Keller et al., ; McKown et al., ; Savolainen, PyhĂ€jĂ€rvi, & KnĂŒrr, ; Soolanayakanahally, Guy, Silim, Drewes, & Schroeder, ) are attractive for the study of adaptive introgression.…”
Section: Introductionmentioning
confidence: 99%
“…Hybridization also results in the sharing of maternally inherited genotypes between closely related species and reduces interspecific divergence of the nuclear ITS sequences through concerted evolution, although the genomic makeup of the current individuals lacks any obvious introgressive signature (Currat et al, ; Du et al, , ; Abbott et al, ; Abbott, ). After excluding all potential hybrids indicated by SSR markers, we found that most cpDNA haplotypes recovered for Rh.…”
Section: Discussionmentioning
confidence: 99%